The evolution of agriculture in the Papua-Papua New Guinea frontier, Keerom District, Indonesia - AKHMAD KADIR; SUHARNO SUHARNO; R. MARSUKI ISWANDI; LA ODE ALWI (Smujo International, 2025)
Abstract. Kadir A, Suharno, Iswandi RM, Alwi LO. 2025. The evolution of agriculture in the Papua-Papua New Guinea frontier, Keerom District, Indonesia. Asian J Agric 9: 554-567. A community's socio-cultural characteristics influence how agricultural systems evolve to support livelihoods. In rural and inland areas, such as in Keerom District, Papua Province, Indonesia, food security is heavily reliant on the availability of natural resources. The local communities in Keerom maintain a hunting-gathering culture and the traditional agricultural systems. This study aims to determine how the agricultural sector in Keerom has developed to meet the needs of people on the border with Papua New Guinea. This includes introducing oil palm and corn as new efforts to develop superior commodities. A survey was conducted using qualitative research techniques and interview methods. The survey analyzed the social, economic, and ecological systems that underlie the evolution of livelihood systems in the region. Data were collected through in-depth interviews with traditional farmers, indigenous community leaders, migrant communities, and other stakeholders, supplemented by field observations. The findings reveal a significant shift in livelihood systems, rooted in evolutionary developments since the time of the ancestors of the Keerom community. This transformation is closely tied to the community's hunting-gathering culture, traditional agricultural practices, the introduction of modern agriculture, the establishment of oil palm plantations, and the implementation of the central government's food estate program. The study highlights that oil palm and corn cultivation present substantial economic opportunities, particularly in terms of income generation and infrastructure development. However, these benefits are accompanied by notable challenges, including shifts in traditional cropping patterns, land tenure conflicts, and adverse impacts on local biodiversity. This research contributes to a deeper understanding of how the integration of new commodities reshapes the agrarian and social landscapes in Keerom District. It also provides insights into the implications for sustainable agricultural development policies in the region, offering a promising path forward for the community and its stakeholders.